2010
DOI: 10.1145/1658349.1658352
|View full text |Cite
|
Sign up to set email alerts
|

Spatial learning and navigation using a virtual verbal display

Abstract: We report on three experiments that investigate the efficacy of a new type of interface called a virtual verbal display (VVD) for nonvisual learning and navigation of virtual environments (VEs). Although verbal information has been studied for routeguidance, little is known about the use of context-sensitive, speech-based displays (e.g., the VVD) for supporting free exploration and wayfinding behavior. During training, participants used the VVD (Experiments I and II) or a visual display (Experiment III) to sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…There are several challenges faced by these sensor-based technologies in indoor environments [16,31], e.g., the high cost of infrastructure construction, the accuracy of localization, and the reliability of signals in complex indoor environments. Moreover, sensor-based localization methods normally anchor the user's location on a 2D map, which requires the users to interpret the map and associate it with the egocentric perception of the environment [18].…”
Section: Introductionmentioning
confidence: 99%
“…There are several challenges faced by these sensor-based technologies in indoor environments [16,31], e.g., the high cost of infrastructure construction, the accuracy of localization, and the reliability of signals in complex indoor environments. Moreover, sensor-based localization methods normally anchor the user's location on a 2D map, which requires the users to interpret the map and associate it with the egocentric perception of the environment [18].…”
Section: Introductionmentioning
confidence: 99%
“…Separately, a rich literature on narrative processing has revealed that verbal descriptions of unobserved environments can be effective for generating accurate mental models of environments and routes (Brunyé, Rapp, & Taylor, 2008;Brunyé, Taylor, & Worboys, 2007; Brunyé & Taylor, 2008a, 2008b; Lee & Tversky, 2005; Mani & Johnson-Laird, 1982; Schneider & Taylor, 1999; Taylor & Tversky, 1992a, 1992b), and for online navigation (Giudice et al, 2007, 2010; Meilinger, 2005; Pazzaglia & De Beni, 2001; Tversky & Lee, 1999; but see Wanet-Defalque, Vanlierde, & Michaux, 2001). Here we demonstrate a complementary phenomenon – that in the course of visually encoding an environment, supplementary verbal information is beneficial for reinforcing landmark memory.…”
Section: Methodsmentioning
confidence: 99%
“…For navigation without vision, an example of stereo sound would be the verbal description of "There is a 40 foot hallway to your left" is heard in the left ear as opposed to a monaural sound. When an environment is learned without vision via monaural verbal descriptions, spatial knowledge is impaired relative to sighted navigation (Giudice, Bakdash, Legge, & Roy, 2010), but this detriment can be reversed using spatial audio (Giudice & Tietz, 2008). An additional benefit of stereo sound is that it has lower demands on working memory than monaural sound (Klatzky et al, 2006).…”
Section: Auditory Aidsmentioning
confidence: 99%